The creation of adaptive governance to solve the water crisis: The case of Guanajuato - Susana Suarez; Alex Ricardo Caldera Ortega (European Regional Science Association (ERSA), 2010)
The proposal is based on accepting the premise that says the water crisis is a crisis of governance. In this sense means that the problems relating to access to water and sanitation, soil degradation and depletion of aquatic ecosystems and aquifers or damage and risks are referred to shortcomings in resource management, institutions for the decision making, conflict resolution and coordination among stakeholders to create action. In Mexico, highlights the case of Guanajuato from the local government has included among its strategies to build an institutional framework based on the paradigm of Integrated Water Resources Management (IWRM), from which it has tried to address the water crisis at the regional level seeking a local action, with social participation and including a long-term vision. What both these institutions solve collective action problems from the perspective of adaptive governance? In other words, how this affects institutional arrangement effective participation of stakeholders, promotes a common understanding of the problem, and get management objectives such as sustainability, equity and efficiency?
Keywords: 330